Core-Shell Nanolipid Co-Delivery of Ergothioneine, Curcumin, and Piperine: Integrating Formulation Performance with Human Clinical Evidence for Anti-Inflammatory and Healthy-Aging Applications - Ziraoui, Nour-Eddine; DeLuca, Marco; Cruz, Jayden (Scientific Journal of Technology, 2026)
Background: Ergothioneine, curcumin, and piperine are mechanistically complementary but translationally limited by divergent physicochemical behavior, uneven release kinetics, and bioavailability constraints. We therefore reconstructed a core-shell hierarchical nanolipid system and integrated its formulation performance with available human clinical evidence relevant to the three-active strategy. Methods: We extracted formulation architecture, encapsulation, release, and stability data from the source patent dossier. We then performed a targeted evidence synthesis of published human interventional studies indexed in PubMed and related registry records available through 28 March 2026, focusing on ergothioneine and/or curcumin-piperine trials that reported efficacy or safety outcomes relevant to inflammation, redox biology, tissue integrity, cognition, skin physiology, or functional status. Results: The nanolipid embodiments maintained nanoscale particle size (28.4-47.5 nm in leading embodiments), low PDI (0.087-0.112), strong negative zeta potential (-38.7 to -41.2 mV), and high encapsulation efficiencies for all three actives (>91% in the principal embodiments). The leading embodiment also showed synchronized 24-hour release (~74-78% for all three actives) and strong 12-month activity retention (>93% for all three actives), outperforming multiple comparators. Our evidence synthesis identified published human data showing that ergothioneine improved skin hydration and facial condition markers in healthy women and improved learning-related performance with a favorable safety profile in older adults with mild cognitive impairment. Published curcumin-piperine trials demonstrated improvements in oxidative stress, inflammatory markers, glycemic or hepatic indices, and selected functional outcomes across metabolic syndrome, type 2 diabetes, hemodialysis, inflammatory bowel disease, CABG recovery, and sepsis, while one phase III rheumatoid arthritis maintenance trial was neutral for flare-free survival. Conclusions: We interpret the formulation dataset and human evidence base together as a coherent translational signal: the spatially partitioned nanolipid carrier addresses major formulation liabilities, while the published clinical literature supports biological plausibility for anti-inflammatory and healthy-aging applications. A direct randomized trial of the exact triad carrier remains the key next step.